Impact of KOH Compound Immersion on Mechanical Properties of Sansivera Fiber Composite: Dampak Perendaman Serat Sansivera dalam Senyawa KOH terhadap Sifat Mekanik Komposit - Ramadhani, Aditya; Widodo, Edi (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the influence of immersing sansivera fibers in varying ratios of KOH compounds on the mechanical properties of the composite. The methods involve KOH preparation, composite fabrication, and tensile testing with six specimens. Results indicate that a 20% KOH mixture yields the highest values: tensile stress strength of 275N/mm², tensile strain of 3.7mm, elastic modulus of 4910.7N/mm², and maximum load of 42.3N. The immersion of sansivera fibers in the KOH compound mixture significantly affects the composite's mechanical characteristics. Highlights: Study on the impact of KOH compound immersion on mechanical properties of the composite. Varying KOH compound ratios (10%-60%) and their influence on tensile stress strength, elastic modulus, and maximum load. Identification of the optimal 20% KOH mixture with the highest mechanical properties.